The Integration Of Islamic Values And Biology Education Using Pedagogical Content Islamic Knowledge (PCIK) - Herlanti, Yanti; Noor, Meiry Fadilah; Zein, Nadya (Jurnal Tarbiyatuna, 2022)
The integration of values is the mission of all Islamic Religious Colleges (IRC) in Indonesia, but many non-Islamic lecturers have not obtained the required model. Therefore, this study aims to create a model for integrating Islamic values with biology learning. The Define, Design, Develop and Disseminate method was used to review the developed documents. Furthermore, a Shared Integration Model known as Pedagogical Content Islamic Knowledge (PCIK) was developed. The result was assessed by two Islamic science experts, resulting in a Cohen’s Cappa coefficient of 0.61. A Senior High School Biology teacher and a lecturer assessed the feasibility of integrating materials and pedagogy, resulting in Cohen’s Cappa coefficient of 0.67. Furthermore, the results were uploaded on a website, tested, and disseminated. The insight into the spiritual value of students who used the PCIK development product is more varied. The dissemination results during the Covid-19 Pandemic showed improvements in the knowledge and competencies in integrating Islamic values and Biology as well as in Biology and pedagogy.